"Why I monitor": World-class endurance coaches` perspectives of athlete monitoring - Timmerman, W.; Stanley, M.; Abbiss, C.; Lawler, N.; Raynor, A. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Athlete monitoring literature tends to focus on the tools and techniques of data collection and analysis, however there is a current lack of understanding as to why coaches implement these tools in their coaching. Therefore, the purpose of this research project was to elicit insights into why world-class endurance coaches conduct athlete monitoring practices. METHODS: A qualitative descriptive research design was employed, using semi-structured interviews (Sandelowski, 2010). Twelve male coaches across canoeing, road and track cycling, rowing, triathlon, and swimming from Australia, Canada, Italy, South Africa, Spain, the USA, and the UK with 16.8 ± 6.4 years of experience were recruited. Eligible participants coached at least one endurance athlete to a top-3 performance in Major Games, World Championship, or cycling Grand Tour. The interview transcripts were analysed inductively using the iterative process of reflexive thematic analysis (Braun & Clarke, 2022). Rigour has been addressed through prolonged engagement with the data, peer examination where co-authors acted as critical friends, dense descriptions of the participants and research methods, and a documented audit trail of the research decisions. RESULTS: The analysis generated five themes "Athlete involvement", "Tracking progress", "Learning and understanding", "Decision making", and "Achieving athletic potential". Tracking athletes` progress provides information to improve the coaches` understanding of their athletes and lead to more informed and contextualised decisions. The coaches perceive that athlete monitoring improves their decision-making to drive and adjust the training program while reducing negative training consequences, such as injury or illness, which is expected to contribute to athletes achieving their potential. Athlete monitoring is also used as a strategy to keep the athletes more closely engaged with their training process. CONCLUSION: The in-depth insights gained from this study indicate that athlete monitoring has various important roles for world-class endurance coaches. For sports scientists, understanding the various purposes and nuances of athlete monitoring can assist them in providing suitable information at the right time to the coach, thus impacting the decision process and athlete`s performance. Future research can explore how world-class coaches use athlete monitoring information to make decisions to refine the training program for the individual athlete and assess the impact coach background, coach-athlete relationship, and athlete information availability and presentation have on coaches` decision-making process and outcomes.